2011
DOI: 10.1620/tjem.224.29
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin as a Key Mediator for Vasculogenic Mimicry in Hepatocellular Carcinoma

Abstract: Osteopontin (OPN) is overexpressed in a variety of cancers including hepatocellular carcinoma (HCC), and is likely involved in the process of vasculogenic mimicry (VM) in some tumor cells. In this study, we explored whether OPN plays a role for VM in HCC. Metastatic MHCC97-H human HCC cells and nonmetastatic Hep3B human HCC cells were compared for their abilities to establish VM. Three dimensionalculture assays showed that MHCC97-H cells but not Hep3B cells were able to form the chord-like structure that repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Interestingly, we showed recently that PLAUR is selectively overexpressed in macrophages that infiltrate adipose tissue in obese subjects and we observed that its circulating levels were associated with markers of insulin sensitivity [32]. The plasminogen-activating system has been involved in liver injury such as fibrosis or cancer [33,34]. Whether components of this system produced by dSAT could contribute to aggravated stages of liver alteration in obesity may deserve future consideration.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, we showed recently that PLAUR is selectively overexpressed in macrophages that infiltrate adipose tissue in obese subjects and we observed that its circulating levels were associated with markers of insulin sensitivity [32]. The plasminogen-activating system has been involved in liver injury such as fibrosis or cancer [33,34]. Whether components of this system produced by dSAT could contribute to aggravated stages of liver alteration in obesity may deserve future consideration.…”
Section: Discussionmentioning
confidence: 93%
“…All primers were synthesized by TaKaRa Biotechnology (Japan). Data were analyzed according to the comparative Ct method [17] and were normalized by β-actin expression in each sample. Relative mRNA levels were calculated based on the Ct values, corrected for β-actin expression, according to the equation: 2-△Ct [△Ct = Ct(TNF-α, IL-1β, IL-6 or IL-10) − Ct(β-actin)].…”
Section: Measurement Of Related Cytokine Concentrations In Serum and mentioning
confidence: 99%
“…The qPCR was carried out with the specific primers (Table 1). All data were calculated based on the comparative Ct formula (Liu et al, 2011b) and each sample was normalized by β-actin. Relative mRNA expressions were analyzed according to the Ct values, based on the equation: 2 À ΔCt [ΔCt ¼ Ct (PKC, JNK, caspase-3, caspase-8)-Ct (β-actin)].…”
Section: Rna Isolation and Qpcr Assaysmentioning
confidence: 99%